Does the crisis change the nature of agglomeration economies in Indonesia? A productivity analysis of pre-post 1997-1998 financial crisis - Khoirunurrofik Khoirunurrofik (REGION, 2020)
By examining their source and magnitude, this paper looked at the changes in the nature of Indonesia's agglomeration economies over three distinct, successive periods: the pre-crisis boom (1990-1996), the deep crisis (1997-2000), and the post-crisis recovery (2001-2010). We found that economies of localisation and urbanisation are both present during the observation periods, with the former generating a stronger effect than the latter. Furthermore, types of agglomeration externalities have significant relationship with variations in size of plants and industrial sectors. These factors shed some light on the nature of agglomeration economies and how the agglomeration sources changed across the crisis periods in favour of localisation economies. The results also demonstrate the industry life cycle at work, as evidenced by changing industry structure during the recovery period.
Keywords: R11; R12; R30; L25; L60; 330; Industry; agglomeration economies; economic cycles; financial crisis; Indonesia